Peranan Dana Desa Dalam Pertumbuhan Ekonomi Kabupaten Di Provinsi Jawa Tengah - Fahmi, Anisa (Jurnal Pendidikan Ekonomi (JUPE), 2025)
In 2023, Central Java Province received the largest allocation of village funds. However, among the 29 regencies in Central Java, no region has achieved the status of an Independent Village (Desa Mandiri). Additionally, the economic growth rate of Central Java Province over the past four years has been lower than the national growth rate, and four regencies in Central Java have an average growth rate below that of the province. This study aims to analyze the impact of village funds on the economic growth of regencies in Central Java Province using data from 29 regencies during the 2018–2023 period. The results of the path analysis estimation show that village funds have a significant negative direct effect on economic growth. The use of village funds tends to be suboptimal in supporting economic acceleration. However, village funds have a positive impact on physical capital, such as infrastructure, as well as on human capital, represented by the increase in the Human Development Index (HDI). Although physical and human capital have been proven to contribute to economic growth, the indirect effect of village funds through these two factors is not significant.